Neurosurgery in a patient at peak levels of rivaroxaban: taking into account all factors. Issue 2 (10th August 2017) - De Vlieger, Jan; Dietvorst, Sofie; Demaerel, Rik; Verhamme, Peter; Nuttin, Bart; Vanassche, Thomas
Abstract: Essentials There is scant data on surgery shortly after intake of rivaroxaban. We performed neurosurgery using high dose PCCs and tranexamic acid. Intraoperative haemostasis was good and no transfusion was needed. There was no delayed postoperative haemotoma or thromboembolic complication. We present a patient who underwent urgent neurosurgery for acute onset paraplegia due to a spontaneous subdural spinal hematoma less than 5 hours after she had taken rivaroxaban. The Key Clinical Question was whether early high‐risk surgery on a patient taking direct oral anticoagulants is feasible. Prothrombin complex concentrate (PCC) and tranexamic acid were administered and perioperative hemostasis was good. There is scant data on neurosurgical procedures performed within 12 hours after the intake of a direct oral anticoagulant. With the hemostatic support of high‐dose PCC, early surgery after administration of rivaroxaban seems feasible in case of an emergency indication, but should only be considered when delaying surgery is esteemed hazardous to the patient. More experience is needed to allow balancing risks and benefits of urgent vs delayed intervention and on the optimal hemostatic support in the absence of a specific antidote.